Raman Spectroscopy of Two-Dimensional Materials - Tan, Ping-Heng.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book shows the electronic, optical and lattice-vibration properties of the two-dimensional materials which are revealed by the Raman spectroscopy. It consists of eleven chapters covering various Raman spectroscopy techniques (ultralow-frequency, resonant Raman spectroscopy, Raman imaging), different kinds of two-dimensional materials (in-plane isotropy and anisotropy materials, van der Waals heterostructures) and their physical properties (double-resonant theory, surface and interface effect). The topics include the theory origin, experimental phenomenon and advanced techniques in this area. This book is interesting and useful to a wide readership in various fields of condensed matter physics, materials science and engineering.
Raman spectroscopy of monolayer and multilayer graphenes -- Raman spectroscopy of isotropic two-dimensional materials beyond graphene -- Raman spectroscopy of anisotropic two-dimensional materials -- Raman spectroscopy of van der Waals heterostructures -- Disorder and defects in two-dimensional mate-rials probed by Raman spectroscopy -- Raman Spectroscopy Study of Two-Dimensional Materials under Strain -- Double resonance Raman spectroscopy of two-dimensional materials -- Raman signatures of surface and interface effects in two-dimensional layered materials: theoretical insights -- Resonant Raman Spectroscopy of Two Dimensional Materials beyond Graphene -- Ultralow-frequency Raman spectroscopy of two-dimensional materials -- Raman imaging of two dimensional materials.
Keywords: Materials -- Analysis; Spectrum analysis; Nanotechnology; Characterization and Analytical Technique; Spectroscopy; Nanotechnology